The Probiotic Lactobacillus sakei Subsp. Sakei and Hawthorn Extract Supplements Improved Growth Performance, Digestive Enzymes, Immunity, and Resistance to the Pesticide Acetamiprid in Common Carp (Cyprinus carpio) - Abdul-Hassan Mahdi Salih; Indrajit Patra; Ramaswamy Sivaraman; Rahim Alhamzawi; Kakhor M. Khalikov; Zahraa Haleem Al-qaim; Sahar Golgouneh; Mohammed Abed Jawad; Ali Hussein Adhab; Andrés Leonardo Vázquez-Cárdenas; Safoura Abarghouei (Aquaculture Nutrition)
This study evaluated the impacts of the probiotic, Lactobacillus sakei (L. sakei), and the extract of hawthorn, Crataegus elbursensis, on growth and immunity of the common carp exposed to acetamiprid. Fish (mean±SE: 11.48±0.1 g) feeding was done with formulated diets (T1 (control): no supplementation, T2: 1×106 CFU/g LS (Lactobacillus sakei), T3: 1×108 CFU/g LS, T4: 0.5% hawthorn extract (HWE), and T5: 1% HWE) for 60 days and then exposed to acetamiprid for 14 days. The growth performance improved in the fish fed LS at dietary level of 1×108 CFU/g, even after exposure to acetamiprid (P<0.05). Intestinal Lactobacillus sakei (CFU/g) load increased (P<0.05), following supplementation with the probiotic-enriched diet. The LS-treated fish had increases in the activity of digestive enzymes (P<0.05). Both LS and HWE stimulated antioxidant enzymes and immune system components in serum and mucus (alkaline phosphatase (ALP), protease, total Ig, and lysozyme) (P<0.05). However, the changes were different depending on the kind of the supplement. The malondialdehyde (MDA) levels decreased in HWE-treated fish after acetamiprid exposure (P<0.05). Both LS and HWE reduced the liver metabolic enzymes (LDH, ALP, AST, ALT, and LDH) in serum both before and after exposure to the pesticide (P<0.05). However, each enzyme exhibited a different change trend depending on the type of the supplement. HWE showed a stress-ameliorating effect, as glucose and cortisol levels declined in the HWE-treated fish (P<0.05). This study indicated the immunomodulatory impacts of LS (1×108 CFU/g) and HWE (at dietary levels of 0.5–1%). The probiotic showed more performance compared to HWE. However, the HWE mitigated oxidative stress more efficiently than the probiotic.